Anesthetic success of 1.8ml lidocaine 2% for mandibular tooth extraction. A pilot study - Pedro Aravena; Nicol Bustos; Andrea Cerón; Viviana Castillo; Claudio González (Universidad de Concepción., 2013)
Aim: To determine the anesthetic effect of a 1.8ml cartridge of anesthetic lidocaine 2% with epinephrine 1:100,000 in inferior alveolar nerve block (NAI) for the extraction in mandibular teeth. Material and methods: A pilot study with analitic design. Participating patients of Dental Emergency Service volunteers from Valdivia-Chile for mandibular teeth extractions attending between May and July of 2010. The anesthetic technique was performed by a dentist using only one cartridge of anesthetic to the NAI. After 15 minutes, the effect was considered effective when anesthetic not require reinforcement with additional anesthesia during extraction of teeth. We analyzed the relationship between success anesthetic effect with sex, age, diagnosis of tooth and type and level of pain observed (chi-square and logistic regression, p<0.05). Results: 62 patients were selected, of which only 47(75.8%) was achieved anesthetic success. There was no statistical association with sex, age, type or dental diagnosis and perceived pain. Conclusion: Using a 1.8ml cartridge of anesthesia was effective in three of four patients treated by extraction of mandibular teeth. It suggests further research in relation to the clinical effectiveness of other anesthetics with the same dose in NAI.